2003
DOI: 10.1152/ajpcell.00372.2002
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-stimulated trafficking of ENaC in renal cells requires PI 3-kinase activity

Abstract: AlphaENaC-EGFP (enhanced green fluorescent protein-tagged alpha-subunit of the epithelial Na(+) channel) stably transfected clonal lines derived from the A6 parental cell line were used to study the physical mechanisms of insulin-stimulated Na(+) transport. Within 1 min of insulin stimulation, ENaC migrates from a diffuse cytoplasmic localization to the apical and lateral membranes. Concurrently, after insulin stimulation, phosphatidylinositol 3-kinase (PI 3-kinase) is colocalized with ENaC on the lateral but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
123
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 18 publications
9
123
3
Order By: Relevance
“…Serum stimulation might therefore "prime" H441 cells and thus allow PI3K to contribute control G Na . However, some renal cell lines clearly display basal Na ϩ transport when deprived of serum/hormones, and it is clear that insulin/PI3K can regulate Na ϩ transport in these cells (2,7,8,37,40), indicating that the priming effect described here is not necessary in all experimental systems. Moreover, in renal cells, insulin has no effect on the Na ϩ current induced by constitutively active SGK1 (2, 4), whereas the SGK1-S422D-induced Na ϩ current reported here was clearly enhanced by insulin.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Serum stimulation might therefore "prime" H441 cells and thus allow PI3K to contribute control G Na . However, some renal cell lines clearly display basal Na ϩ transport when deprived of serum/hormones, and it is clear that insulin/PI3K can regulate Na ϩ transport in these cells (2,7,8,37,40), indicating that the priming effect described here is not necessary in all experimental systems. Moreover, in renal cells, insulin has no effect on the Na ϩ current induced by constitutively active SGK1 (2, 4), whereas the SGK1-S422D-induced Na ϩ current reported here was clearly enhanced by insulin.…”
Section: Discussionmentioning
confidence: 87%
“…These observations are consistent with a body of data that highlights SGK1 as an important regulator of G Na in absorptive epithelia (1-3, 31, 49 -51, 53, 57). Although it is clear that glucocorticoid hormones do induce SGK1 expression (31), SGK1 is an important downstream target of PI3K (29), and data from several absorptive cell types have suggested that insulin can increase the apical abundance of ENaC via a mechanism dependent on a PI3K-mediated increase in SGK1 activity (2,8,46,51). Moreover, PIP 2 and PIP 3 also activate ENaC by binding to the channel complex, and this provides another mechanism by which PI3K-coupled agonists, such as insulin, can stimulate Na ϩ transport (20,42,43,52).…”
Section: Discussionmentioning
confidence: 99%
“…Section 1734 solely to indicate this fact. 4 The abbreviations used are: ENaC, epithelial sodium channel; siRNA, short interfering RNA; PI3K, phosphatidylinositol 3-kinase; FRT, Fischer rat thyroid; RT, reverse transcription; Sgk, serum-and glucocorticoid-dependent kinase; PDK, phosphoinositide-dependent protein kinase. …”
mentioning
confidence: 99%
“…Transepithelial Na ϩ absorption across the kidney distal collecting duct, the distal colon, and the ducts of the exocrine glands occurs via the epithelial sodium channels (ENaC) 4 and is tightly regulated by hormones such as aldosterone, insulin, and arginine vasopressin. These hormones play an important role in Na ϩ and fluid homeostasis, and their activities are critical in the regulation of blood pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation